The Influence of Technology-Based Learning Strategies on Student Performance/Motivation in Primary Schools - Bulan Widyadhari (International Journal of Students Education, 2024)
In today’s digital era, the use of technology in education is becoming increasingly important. Technology-based learning strategies (e-learning) have become an effective method for improving student performance, especially in elementary schools. This journal aims to explore and analyze the influence of technology-based learning strategies on the performance of content data from surveys and interviews with teachers and students. The research results show that students in elementary schools are able to use technology . This study uses literature review methods and qualitative methods, including analysis of student use of technology in learning can increase student motivation and engagement, thereby improving their academic performance. Apart from that, technology-based learning strategies can also help in preparing students for an increasingly digital future. However, this research also found several challenges, such as limited access to technology and difficulties in integrating technology into the school curriculum. Therefore, this research suggests that the development of technology-based learning strategies must be adapted to school needs and conditions, and ensure that all students have equal access to technology. The research method chosen was the document review method. Data collection was carried out by recording and reviewing research articles related to the use of technology-based learning media in elementary schools, which were then analyzed and appropriate conclusions were drawn. with research objectives. The conclusion of this research is that the benefits of implementing e-learning now can be felt so that teachers and students feel the need to study the Koran in depth.